Integration Of Fingerprint Centre Point Location And Principal Component Analysis For Fingerprint Verification - Chan, Ying Hui; Abu Bakar, Syed Abdul Rahman (Penerbit UTM Press, 2005)
This Paper Presents An Efficient Algorithm For Estimating The Location Of The Centre Point (Cp) Of A Fingerprint For The Purpose Of Aligning Fingerprints In A Fingerprint Verification System. Principal Component Analysis (Pca) Is Utilized In This System. The Proposed Cp Estimation Algorithm Is Based On The Alteration Tracking (At) Followed By An Estimation Algorithm. At Is Proposed To Extract A Track That Records The Transition From One Quantized Direction To Another While The Centre Point Estimation (Cpe) Algorithm Is Used To Find The Bending Point With Highest Direction Transition From The Transition Track. Fingerprint Feature Extraction Is Obtained With Respect To The Cp Of The Fingerprint Directional Field. Pca Is Then Performed Over The Centred Fingerprint Directional Field To Extract Important Information From Fingerprint Features For Verification Purpose. Experimental Result Shows That The Proposed Cp Algorithm Is Capable Of Reliably Aligning Fingerprints. Furthermore, Pca Is Able To Extract Information From Aligned Fingerprint Directional Field For Fingerprint Verification.